Improving Students Vocabulary Mastery By The Used Of Mnemonic Technique - Muhammad Syahrip; Ibrahim Manda; Andi Sadapotto; Sam Hermansyah; Buhari Buhari (La Ogi : English Language Journal, 2022)
This research aims improving students vocabulary mastery by the used of mnemonic technique at seventh grade smp negeri 3 dua pitue kalosi, In this research we use quantitative research methods, quantitative research methods are a process of finding knowledge that uses data in the form of numbers as a tool to analyze information about what the researcher want to know.The population of this research is the seventh grade students of SMP 3 Dua pitue kalosi, The instruments used in this study were pre test and post test. Instrument The research calculate the mean score, find out standard deviation of the test, compute the frequency and the rate percentage of the students’ score and testing the hypothesis of the significant difference between some independent variable by calculating the value of independent t-test use SPSS. the mean score of the students in post-test (65.36) was greater than pre-test (37.93), it means that the students who was teach by using mnemonic technique in teaching vocabulary was improve.